Grid Forming Stator Flux Control of Doubly-Fed Induction Generator - Norbert Klaes; Florian Pöschke; Horst Schulte (Energies, 2021)
The doubly fed induction generator is widely used in wind power applications. For stand-alone operation of this machine, the control of the stator flux with fixed voltage and frequency has been proposed. This paper extends the stator flux control of the doubly fed induction machine by droop mechanisms, which vary the setpoint of flux magnitude and frequency depending on active and reactive power. This gives the doubly fed induction generator system unknown grid supporting and grid forming performance. The validation of the proposed control scheme has been conducted on a <semantics>10<mspace width="3.33333pt"></mspace>kVA</semantics> testbed system. The closed-loop behavior of the system has been proven to enable grid-tied and islanded operation with the same control structure. The system response to load changes and islanding events show no disruptive transients in both conditions.